Antibody engineering: beginnings to bispecifics and beyond - Wilkinson, Ian (Henry Stewart Talks, 2019)
Introduction to antibodies and their use in therapy, Antibody structure and function, Antibody engineering, Humanization, Antibody fragments, Fc engineering, Half-life extension, Modulation of Fc effector function, Glycoengineering, Bispecific antibodies, Antibody drug conjugates, Fc fusion proteins, Immunokines, Future developments in antibody engineering